Evaluasi Program Kurikulum Dalam Meningkatkan Mutu Pendidikan Di MAS AL-Washliyah 22 Tembung - Sri Andriani; Inom Nasution; Rismoninta Padang; Ihsan Saraini; Tria Indah Ristika; Bella Bunda; Suci Ramadani (Universitas Muhammadiyah Enrekang, 2023)
The evaluation of curriculum program in improving the quality of education is motivated by the development of increasingly sophisticated and globalized science and technology (IPTEK), so that it has an impact on almost all human life on earth today, including educational institutions. Educational institutions are required to be able to anticipate these changes by realizing quality education. In education management, curriculum management needs to be carried out by holding and applying the existing management principles so that the output produced is of quality. The purpose of this study was to determine how the evaluation of curriculum program in improving the quality of education at MAS Al-Washliyah 22 Tembung. This research uses a qualitative approach with the type of case study research. Data collection is done by observation, interviews, and documentation. The results of the research at MAS Al-Washliyah 22 Tembung are: (1) curriculum program planning in improving the quality of education at MAS Al-Washliyah 22 Tembung has been carried out collaboratively, meaning that by involving school personnel in all stages of curriculum planning; (2) the implementation of the curriculum program in improving the quality of education at MAS Al-Washliyah 22 Tembung has been carried out in accordance with the general principles of curriculum development; (3) the evaluation of the curriculum program in improving the quality of education at MAS Al-Washliyah 22 Tembung is carried out very well, as evidenced by the existence of a systematic effort in setting implementation standards.